2005
DOI: 10.1016/j.ydbio.2005.07.031
|View full text |Cite
|
Sign up to set email alerts
|

hecate, a zebrafish maternal effect gene, affects dorsal organizer induction and intracellular calcium transient frequency

Abstract: A zebrafish maternal effect mutation, in the gene hecate, results in embryos that have defects in the formation of dorsoanterior structures and altered calcium release. hecate mutant embryos lack nuclear accumulation of beta-catenin and have reduced expression of genes specific to the dorsal organizer. We found that hecate mutant embryos exhibit a nearly 10-fold increase in the frequency of intracellular Ca2+ transients normally present in the enveloping layer during the blastula stages. Inhibition of Ca2+ rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 54 publications
7
52
1
Order By: Relevance
“…Previous work has shown that high levels of bmp activity lead to a reduction in the dorsally and animally oriented movements associated with convergence and axis extension, respectively (Myers et al, 2002a). Consistent with these results, hec mutant embryos have a marked expansion of bmp expression during the gastrula stages (Lyman Gingerich et al, 2005). Thus, the vegetally directed movement of the hec mutant cells before somitogenesis leads to an expansion of the ventroposterior region.…”
Section: Gene Expression Boundary Organization In the Posterior Regiosupporting
confidence: 78%
See 4 more Smart Citations
“…Previous work has shown that high levels of bmp activity lead to a reduction in the dorsally and animally oriented movements associated with convergence and axis extension, respectively (Myers et al, 2002a). Consistent with these results, hec mutant embryos have a marked expansion of bmp expression during the gastrula stages (Lyman Gingerich et al, 2005). Thus, the vegetally directed movement of the hec mutant cells before somitogenesis leads to an expansion of the ventroposterior region.…”
Section: Gene Expression Boundary Organization In the Posterior Regiosupporting
confidence: 78%
“…1c, asterisk). These cells have been described previously in axis-defective embryos caused by either vegetal ablation (Mizuno et al, 1999;Ober and Schulte-Merker, 1999) or maternal-effect mutations (Kelly et al, 2000;Nojima et al, 2004;Lyman Gingerich et al, 2005), but their origin has not been explained. hec mutant embryos with less severe phenotypes also show dorsoanterior defects, although of correspondingly lesser degrees (Fig.…”
Section: Resultsmentioning
confidence: 72%
See 3 more Smart Citations